Microkinetic modeling of DME synthesis from methanol over H-zeolite catalyst: Associative vs. dissociative pathways - Park, Jongmin; Cho, Jiyeong; Park, Myung June; Lee, Won Bo (Catalysis Today, 2021)
In this study, the reaction pathways of DME synthesis by methanol dehydration over a H-zeolite catalyst were analyzed through both computational chemistry and microkinetic modeling methods. The reaction mechanisms consisted of nine forward and backward elementary-step reactions for both associative and dissociative pathways. Based on the second-order Møller–Plesset perturbation theory (MP2), to determine the effects of dispersion forces that were important in our reaction system, the structures of all related reaction species were optimized, and the transition states of the associative and dissociative pathways were elucidated. Also, the energies and activation barriers of the optimized structures and transition states were calculated. Then, a microkinetic model was developed using the energies and activation barriers obtained from the MP2 calculations. Meanwhile, the pre-exponential factors of the kinetic parameters were not calculated theoretically but estimated by fitting the experimental data, which enhanced the reliability of the microkinetic model. By comparing the relative elementary-step reaction rates calculated using the developed model, the dissociative pathway was suggested as a dominant pathway of DME synthesis, while the DME formation reaction of the dissociative pathway (CH3OH-CH3-Z → CH3OCH3-H-Z) was found to be the rate-determining step. The developed model was also used to evaluate the effects of temperature on the site fractions over the catalyst.
Keywords: Dissociative pathways; DME synthesis; Effects of temperature; Microkinetic modeling; Plesset perturbation theory; Preexponential factor; Rate determining step; Reaction pathways; DME synthesis; Microkinetic model; Møller–Plesset perturbation theory; Parameter estimation; Reaction pathway